2021
DOI: 10.1038/s41598-020-80798-w
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to food and cocaine cues are independent traits in a large sample of heterogeneous stock rats

Abstract: Sensitivity to cocaine and its associated stimuli (“cues”) are important factors in the development and maintenance of addiction. Rodent studies suggest that this sensitivity is related, in part, to the propensity to attribute incentive salience to food cues, which, in turn, contributes to the maintenance of cocaine self-administration, and cue-induced relapse of drug-seeking. Whereas each of these traits has established links to drug use, the relatedness between the individual traits themselves has not been w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 62 publications
1
18
1
Order By: Relevance
“…Prior study mapped several anxiety-like traits using zero maze ( 23 ). GWAS using HS to study behavioral regulation ( 108 ), response to cocaine cues ( 109 ), cocaine ( 110 ), nicotine ( 28 , 81 ), or oxycodone ( 111 ) self-administration are underway. Our study adds to the literature 30 QTLs and 17 candidate genes for psychiatric related behavioral traits.…”
Section: Discussionmentioning
confidence: 99%
“…Prior study mapped several anxiety-like traits using zero maze ( 23 ). GWAS using HS to study behavioral regulation ( 108 ), response to cocaine cues ( 109 ), cocaine ( 110 ), nicotine ( 28 , 81 ), or oxycodone ( 111 ) self-administration are underway. Our study adds to the literature 30 QTLs and 17 candidate genes for psychiatric related behavioral traits.…”
Section: Discussionmentioning
confidence: 99%
“…This represents a challenge for animal models, where the comparatively limited genetic diversity of research subjects may elide some variability factors. Recent work has made use of “heterogeneous stock” rodents – the product of multiple strain crossings - to increase genetic diversity and investigate individual differences in addiction-like behavior and reward learning in the context of drug use ( Hughson et al, 2019 ; de Guglielmo et al, 2021 ; King et al, 2021 ; Sedighim et al, 2021 ). One such study identified a relationship between gut bacterial content and behavioral features of impulsivity and attention ( Peterson et al, 2020 ).…”
Section: Other Considerations For Animal Models Of Substance Use Disordermentioning
confidence: 99%
“…The primary findings, results, and conclusions presented in this paper address a different scientific question than those presented in King et al 2021.…”
Section: Data Availabilitymentioning
confidence: 72%
“…For Conditioned Reinforcement (CRf) the primary measures were total active and inactive responses, total earned lever reinforcers, total lever deflections, and an incentive value index ((responses in active port − responses in inactive port) / lever contacts). We chose to separately examine total lever deflections and lever deflections corrected for total responses, because we have previously shown that these measures are more strongly correlated to the PavCA index (Hughson et al, 2019; King et al, 2021).…”
Section: Methodsmentioning
confidence: 99%